Perubahan warna basis akrilik setelah penggunaan pasta pembersih gigitiruan rosella (The changes of acrylic base color after using roselle pasta denture cleanser) - Evan G. Tunggal; Moh. Dharmautama; Eri H. Jubhari (DiscoverSys Inc., 2015)
This clinical experimental study was aimed to determine the effect of roselle denture cleanser paste usage on acrylicbase color degradation. Acrylic base color degradation was assessed by providing roselle denture cleanser to 5subjects to be used every day. In month 3, 6 and 9, data collection were performed by a professional photographer andassessed by CIELab system. Data were analyzed using Wilcoxon and friedman two ways. Acrylic base color, beforeand after pasta using, showed a statistically significant difference in the 6thand 9thmonth. In conclusion, acrylic basecolor changes after using of pasta for 9 months